Naive Bayes Algorithm to Enhance Sentiment Analysis of Coursera Application Reviews on Google Play Store - Masdarul Rizqi; Martanto; Arif Rinaldi Dikanda; Dede Rohman (Yayasan Kita Menulis, 2025)
Coursera is an online learning platform that provides various courses and certifications. This study aims to analyze user perceptions of the Coursera application after the reviews are translated into Indonesian, identify factors that influence positive and negative sentiment, and activate the effectiveness of the Naive Bayes algorithm in classifying review sentiment. The method used is Knowledge Discovery in Databases (KDD), with stages of data collection, preprocessing, and sentiment analysis using Naive Bayes. The results of the study show that the translation of reviews does not change the essence of user perception. Analysis of key words reveals positive experiences such as